'Diabetes at the front door': meeting the needs of diabetes patients in emergency. (9th June 2020) - Chaplin, Steve
Abstract : The Joint British Diabetes Societies Inpatient Care Group has produced a comprehensive and practical aid for the non‐specialist that covers the medical emergencies most likely for people with diabetes. Steve Chaplin reports.